2010
DOI: 10.1007/s11816-010-0145-0
|View full text |Cite
|
Sign up to set email alerts
|

Pyramiding transgenes for potato tuber moth resistance in potato

Abstract: The feasibility of two strategies for transgene pyramiding using Agrobacterium-mediated transformation was investigated to develop a transgenic potato (Solanum tuberosum L. cv. Iwa) with resistance to potato tuber moth (PTM) (Phthorimaea operculella (Zeller)). In the first approach, cry1Ac9 and cry9Aa2 genes were introduced simultaneously using a kanamycin (nptII) selectable marker gene. The second approach involved the sequential introduction (re-transformation) of a cry1Ac9 gene, using a hygromycin resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…Benefits of GM crops include reduced production costs, increased crop yields, reduced need for pesticides, enhanced nutrient composition and food quality, resistance to pests and disease, greater food security, and medical benefits for a growing world population (Phillips 2008). Introducing transgenes in the nuclear genome of plants using Agrobacterium-based plasmid vectors have caused transformation of a wide range of plant species (Meiyalaghan et al 2010). Agrobacterium-mediated transformation of potato, selection based on kanamycin resistance, and use of the nptII selectable gene marker have proven to be an effective technique for transferring Bt genes (Kumar et al 2010).…”
Section: Potato Transformationmentioning
confidence: 99%
“…Benefits of GM crops include reduced production costs, increased crop yields, reduced need for pesticides, enhanced nutrient composition and food quality, resistance to pests and disease, greater food security, and medical benefits for a growing world population (Phillips 2008). Introducing transgenes in the nuclear genome of plants using Agrobacterium-based plasmid vectors have caused transformation of a wide range of plant species (Meiyalaghan et al 2010). Agrobacterium-mediated transformation of potato, selection based on kanamycin resistance, and use of the nptII selectable gene marker have proven to be an effective technique for transferring Bt genes (Kumar et al 2010).…”
Section: Potato Transformationmentioning
confidence: 99%
“…The simplest approach is by sexual crossing of transgenic lines to achieve the desired pyramided loci for multiple traits such as pest and disease resistance. However, sexual hybridization to pyramid transgenes is unsuitable in clonal crops such as potatoes, and it is necessary to pyramid transgenes in potato either by a simultaneous transformation strategy with multiple genes or by a sequential re-transformation strategy into an existing transgenic line using different selectable marker genes (Meiyalaghan et al, 2010). Pyramiding of the cry1Ac9 and cry9Aa2 genes has been achieved in potato, and although no lines expressing both cry genes exhibited any greater resistance to PTM larvae over that previously observed for the individual genes (Meiyalaghan et al, 2010), it is anticipated that these lines will permit more durable resistance by delaying the opportunities for PTM adaptation to the individual cry genes.…”
Section: Genetic Engineering Case Study: Bacillus Thuringiensis Toxinmentioning
confidence: 99%
“…This marker gene is highly effective and is used almost exclusively for potato transformation. A few studies have reported success with other marker genes such as methotrexate resistance (Jacobs et al ., ), hygromycin resistance (Meiyalaghan et al ., ) and imidazoline (Storck et al ., ). The relative efficiency of recovery of transgenic potato lines using identical vectors with alternative selectable marker genes was summarized as follows: kanamycin resistance > hygromycin resistance > phosphinothricin resistance > phleomycin resistance > methotrexate resistance (Barrell and Conner, ; Barrell et al ., ).…”
Section: Gene Transfer To Potatoes By Transformationmentioning
confidence: 99%
“…Expression of Cry genes in the plastid genome does not require adjustment of codon usage or any other sequence manipulations (McBride et al 1995 ; De Cosa et al 2001 ; Chakrabarti et al 2006 ). Moreover, multiple gene stacking by polycistronic expression of transplastomic chloroplasts would avoid the retransformation and additional selectable marker gene integration in the plant genome by conventional nuclear gene pyramiding via Agrobacterium- mediated gene transfer (Meiyalaghan et al 2010 ). In addition, the absence of insecticidal proteins in transgenic pollen eliminates toxicity to pollen-feeding non-target insects, thereby increasing the efficacy and safety of transgenic plants throughout the growing season (De Cosa et al 2001 ).…”
Section: Pest and Disease Resistancementioning
confidence: 99%